RF quadrupole focusing drift tube linac RF design - Plastun, A.S.; Polozov, S.M. (Вопросы атомной науки и техники, 2012)
Drift tube linacs with quadrupole focusing based on Interdigital H-type (IH) resonators are used at medium energies of proton beams. The linac with spatially periodic quadrupole focusing designed by V.A. Teplyakov (SH-DTL, RFQ-DTL) provides enough energy gain rate and good focusing but it is too sophisticated at tuning. The DTL with magnetic quadrupole focusing is simpler then the first one at tuning but it is deprived of advantages of RF focusing. The IH-DTL linac proposed in Frankfurt University is new perspective but rare system. The new RF quadrupole focusing structure will be proposed in this paper. Such structure consists of periodic sequence of several number of drift tubes and RF quadrupole electrodes, located in the same IH-resonator. Different designs of the structure will be considered. Electrodynamic parameters of the one convenient structure will be determined. New structure will be compared with conventional DTL, RFQ-DTL and IH-DTL linacs.